PENGARUH BEBAN KERJA DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN ( STUDI KASUS PADA KURIR DI PT. RAJAWALI JAYA EXPRESS) - Juwita, Kristin (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The purpose of this study was to determine the effect of workload and work ability on employee performance at PT. Rajawali Jaya Express. Data collection is done by distributing questionnaires. This study uses a quantitative approach with explanatory research methods which are carried out through data collection in the field. The population studied were employees of the courier delivery department,  totaling 37  employees.  The  sampling technique  used  was  the  saturated sample technique. The data analysis method used validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing through t test and coefficient of determination (R2). This study obtained the results that workload has a negative and significant effect on employee performance, while work ability has a positive and significant effect on the performance of courier employees at PT. Rajawali Jaya Express.